Role of maximum and explosive strength in the relationship between the Expanded Disability Status Scale (EDSS) and functional capacity in people with multiple sclerosis: A mediation analysis - Andreu Caravaca, Luis (2025)
The relationship between functional capacity and disability status in individuals with Multiple Sclerosis (MS) is well established. However, to date, the interference of lower limb strength in this classic correlation has not been studied. Therefore, this study aimed to investigate the mediating role of muscle lower limb strength variables, including maximum strength (MVIC) and explosive strength (RFD), in the relationship between the disability status, measured by Expanded Disability Status Scale (EDSS), and functional test outcomes in a MS sample. A total of 49 patients performed 4 functional tests: timed up-and-go test (TUG), sit-to-stand (STS), 10-meter walk test (10MWT), and 6-minute walk test (6MWT), as well as the measurement of MVIC and RFD. A statistical mediation analysis was conducted to examine the influence of maximum and explosive strength on the relationship between EDSS and functional capacity. Regarding MVIC, the effect of EDSS on the 6MWT (indirect effect = 48%, p = .013), 10MWT (indirect effect = 18.1%, p = .015) and TUG test (indirect effect = 27.2%, p = .003) decreased. Regarding RFD late (0–200), the effect of EDSS on the 6MWT (indirect effect = 34.8% p = .0048), 10MWT (indirect effect = 18.0%, p = .021) and TUG test (indirect effect = 25.0%, p = .014) decreased. MVIC and RFD late variables play a significant role and influence the relationship between the EDSS and functional capacity.